2009
DOI: 10.1038/ncb1824
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear signalling by tumour-associated antigen EpCAM

Abstract: EpCAM was found to be overexpressed on epithelial progenitors, carcinomas and cancer-initiating cells. The role of EpCAM in proliferation, and its association with cancer is poorly explained by proposed cell adhesion functions. Here we show that regulated intramembrane proteolysis activates EpCAM as a mitogenic signal transducer in vitro and in vivo. This involves shedding of its ectodomain EpEX and nuclear translocation of its intracellular domain EpICD. Cleavage of EpCAM is sequentially catalysed by TACE and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
770
2
12

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 610 publications
(814 citation statements)
references
References 48 publications
30
770
2
12
Order By: Relevance
“…Epcam expression was predominantly nuclear in tumors (Fig. 2C), but membranous in the biliary epithelial cells present in normal liver, consistent with the proposed mitogenic role of the Epcam intracellular domain after its nuclear translocation (28). The tumor nodules had increased DNA synthesis compared with adjacent normal tissue based on their uptake of BrdU (Fig.…”
Section: Resultssupporting
confidence: 64%
“…Epcam expression was predominantly nuclear in tumors (Fig. 2C), but membranous in the biliary epithelial cells present in normal liver, consistent with the proposed mitogenic role of the Epcam intracellular domain after its nuclear translocation (28). The tumor nodules had increased DNA synthesis compared with adjacent normal tissue based on their uptake of BrdU (Fig.…”
Section: Resultssupporting
confidence: 64%
“…13). EpCAM, also known as CD326, is a 40 kDa type I membrane glycoprotein frequently expressed in human carcinomas, and involved in cell proliferation by linking to components of the Wnt signaling pathway and regulators of the cell cycle (14,15). It initially attracted attention as a target for cancer-related immunotherapy due to its abundant expression in solid tumors, although expression in normal epithelia is low (14)(15)(16)(17), and recent studies further unveiled its association with cancer stem cells (15)(16)(17)(18)(19) and circulating tumor cells (16,18,19).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, tumor cell showed high expression level of PCNA, representing high proliferation stage of hepatic tumors, however, no expression in normal appearing hepatocytes. A recent report showed that regulated intramembrane proteolysis activates EpCAM as a mitogenic signal transducer, resulting elevated expression of c-myc and cyclin A and E (Maetzel et al, 2009).…”
Section: Discussionmentioning
confidence: 99%